2009
DOI: 10.3899/jrheum.090817
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Clinical Outcomes after Intraarticular Injection of a Recombinant Adeno-associated Vector Containing a Tumor Necrosis Factor Antagonist Gene: Results of a Phase 1/2 Study

Abstract: IA rAAV2-TNFR:Fc resulted in administration site reactions after 12% of injections. A fatal SAE, disseminated histoplasmosis, was considered not related to study agent. Patient-reported outcome measures of clinical response showed greater improvement in treated patients than placebo patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 43 publications
3
84
0
2
Order By: Relevance
“…Recombinant AAV is a promising delivery vehicle for articular cartilage with the advantages of sustained transgene expression, reduced potential for host immune response, and the capacity to transduce both dividing and nondividing cells in vivo and in vitro (Ulrich-Vinther et al, 2002;Lee et al, 2011). The viral vector is derived from an endemic, nonpathogenic parvovirus, and intra-articular injection of AAV has been used in clinical trials for delivery of bioactive substances (Mease et al, 2010;High and Aubourg, 2011). Numerous serotypes of AAV exist, each serotype with different preferential targets (Goater et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant AAV is a promising delivery vehicle for articular cartilage with the advantages of sustained transgene expression, reduced potential for host immune response, and the capacity to transduce both dividing and nondividing cells in vivo and in vitro (Ulrich-Vinther et al, 2002;Lee et al, 2011). The viral vector is derived from an endemic, nonpathogenic parvovirus, and intra-articular injection of AAV has been used in clinical trials for delivery of bioactive substances (Mease et al, 2010;High and Aubourg, 2011). Numerous serotypes of AAV exist, each serotype with different preferential targets (Goater et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this fact, only a few clinical trials of this therapeutic strategy have been conducted mainly due to scientific, technological, financial and sociological hurdles (Evans et al, 2011). A single phase II study has been reported recently and this slow pace indicates the unlikelihood of gene therapy to become clinically available in the near future (Mease et al, 2010). One of the most serious reason for the current slow progress in gene therapy research in OA (and RA) lies in the widespread public scepticism with anything relating to genes.…”
Section: Obstacles and Challenges In Clinical Application Of Gene Thementioning
confidence: 99%
“…This concept utilizes viral or non-viral vectors to deliver genetic information encoding biological agents into the target tissue for their local expression. It appears that viral strategies provide high transfection efficiency and many additional assets for a clinical development (Mease et al, 2010) but immunogenicity and possible mutagenicity are their main drawbacks. Non-viral strategies, on the other hand, have a fascinating preclinical development in arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…196 The development of siRNA and shRNA technology opened up infinite 197 possibilities for RNA interference therapeutics. Since the year 2004, 198 more than 50 clinical trials involving 26 different siRNAs have been 199 carried out to treat various conditions from macular degeneration to 200 kidney failure to cancers, etc. [36][37][38].…”
mentioning
confidence: 99%
“…Although lentivirus can target many tissue types, 918 they may confer substantial risk of insertional mutagenesis. One of the t1:1 can be minimized with the use of self-complementary vectors [198] 921 and/or codon-optimized sequences for the expression of transgenes 922 [199].…”
mentioning
confidence: 99%